The Backlash of Globalization - Italo Colantone; Gianmarco I. P. Ottaviano; Piero Stanig (Center for Economic Studies and ifo Institute (CESifo), 2021)
We review the literature on the globalization backlash, seen as the political shift of voters and parties in a protectionist and isolationist direction, with substantive implications on governments' leaning and enacted policies. Using newly assembled data for 23 advanced democracies, we document a protectionist and isolationist shift in electorates, legislatures, and executives from the mid-1990s onwards. This is associated with a noticeable protectionist shift in trade policy –although with some notable nuances– especially since the financial crisis of 2008. We discuss the economics of the backlash. From a theoretical perspective, we highlight how the backlash may arise within standard trade models when taking into account the 'social footprint' of globalization. Then, we review the empirical literature on the drivers of the backlash. Two main messages emerge from our analysis: (1) globalization is a significant driver of the backlash, by means of the distributional consequences entailed by rising trade exposure; yet (2) the backlash is only partly determined by trade. Technological change, crisis-driven fiscal austerity, immigration, and cultural concerns are found to play an important role in creating politically consequential cleavages. Looking ahead, we discuss possible future developments, with specific focus on the issue of social mobility.
Keywords: F10; 330; globalization; social footprint; backlash